HOME IN THE POETRY OF SAUDI ARABIA POETS: KHALID AL-FAISAL AN EXAMPLE OF A DISTINGUISHED ARAB (2) - Dahami, Yahya Saleh Hasan (Islamijah: Journal of Islamic Social Sciences, 2023)
It is well known that when a philosopher articulates his or her love for and affiliation with the homeland, he or she may represent the great homeland through a limited part of this homeland. It is worth noting that Makkah Al-Mukarramah is simply a small, light representation of the great homeland, which embraces Makkah Al-Mukarramah like the heart of the body. Consequently, through the striking poem "Umm Al-Gura" by Khalid Al-Faisal, the researcher wishes to highlight the poet's knowledge while also illustrating his love for his vast landscape, the Kingdom of Saudi Arabia. The researcher, on the other hand, attempts to examine the poet's talent through the use of poetic images and symbols in his poem. The study begins with a brief introduction, followed by a prevue examination of Saudi poetry then a glance at the significance of Makkah Al-Mukarramah. The study's main focus is on the Saudi poet Khalid Al-Faisal with reference to some verse lines of his poem Umm Al-Gura (ام القرى). The study implements a critical-analytical method, keeping in mind the concept of home as its primary concern. A brief discussion and conclusion to the analysis are then given.